Semantic-Pragmatic Analysis of Lexical Units Expressing Negative Intellectual Characteristics in English and Uzbek Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
in this article, on the example of the English and Uzbek languages, the combination of adjective lexemes characteristic of human character, their role in intercultural communication, functional-semantic features are analyzed, and the works of English and Uzbek writers, newspapers and magazines related to the socio-political sphere, explanatory dictionaries and the Internet are used as sources, quality lexemes taken from the materials of the human character.